Fitat dan fitase : dampak pada hewan ternak - Yanuartono Yanuartono; Alfarisa Nururrozi; Soedarmanto Indarjulianto (Faculty of Animal Science, Universitas Brawijaya, 2016)
In countries with high plant biodiversity such as Indonesia, the availability of food of plant origin is very diverse. The presence of anti-nutrients in plants would potentially cause problems in cattle if not managed properly. phytic acid is one anti nutritional factor that have a role in disrupting the health and productivity The term phytate refers to the molecule phytic acid, which generally acts as a chelate to Mg, Ca, Na, and K, and in some cases protein and carbohydrates. Seeds of cereals, legumes and oilseed plant which is used as animal feed usually contains a lot of phytic acid which can cause a decline in nutritional value. However, with a variety of processing methods, levels of phytic acid in animal feed can be reduced or even eliminated. In addition to the processing method, the method of adding phytase enzyme may also be done to improve the nutritional value of the animal feed ingredients.Keywords:anti-nutrients.phytic acid. processingmethods.phytase